The American Presence in Iraq and its Impact on the Variables (Politically, Economically and Socially) - Abdullah, Nisreen Ahmed (Journal of Humanities & Social Sciences, 2020)
Through the search, I found The United States of America had a major impact on the situation in Iraq after 2003, And in all political, economic and social fields, This became clearly visible in his internal and external interference with the state This gave the wide scope to the regional states in their clear interference to the sovereignty of Iraq.and Realistic scientific method was adopted in this research The study reached the results that the United States of America wanted to seize the wealth of Iraq and plunder its resources, and what is meant is the oil that Iraq is blessed with. The study also recommended several recommendations, the most important of which is the necessity of working to unify Arab and international efforts in order to eliminate the most important negative effects resulting from the American occupation of Iraq and work to restore human and economic capacity within society, the most important of which are the oil sources that serve all Arab countries.